Clinical case – medulloblastoma - Kablytė , A.; Gleiznienė , R. (Neurologijos seminarai, 2018)
In this article we present a clinical case of malignant neuroectodermal tumor – medulloblastoma manifestation in a pediatric patient. This type of tumor occurs mostly in infants, and it is more common among boys than girls. Usually in clinical practice, same as in our case, the main clinical symptoms are behavioral changes, sluggishness, nausea, vomiting and headache caused by elevation of intracranial pressure due to obstructive hydrocephalus. Although tumor biopsy remains the gold standard for the diagnosis of medulloblastoma, diagnostic imaging methods such as computed tomography (CT) and magnetic resonance imaging (MRI) are very important as well. These medical imaging techniques give us a lot of necessary information about tumor localization in posterior cranial fossa and dissemination in surrounding brain tissue. This in formation is helpful when deciding what treatment option is the finest in a specific clinical case. Also, it is useful to evaluate postoperative brain tissue, whether the tumor resection was radical or not.
Keywords: central nervous system tumors; posterior cranial fossa; cerebellum; medulloblastoma